Analysis and simulation of handoff scenario for wireless communication network / Darul Ridzuan Muhamad Halib - Muhamad Halib, Darul Ridzuan (2006)
This project presents an overview of the handoff scenario for wireless communication network. Handoff is an essential element of wireless communications. Efficient handoff algorithms are a cost-effective way of enhancing the capacity and QoS of wireless systems. This project presents different aspects of handoff and discusses handoff related features of cellular systems. It involved a brief study of the various parameters affecting the handoff procedure. It includes a Matlab implementation of the received power (with gaussian noise) versus the distance in the soft handoff case for a mobile moving between two base stations separated by distance d, along a straight line with fixed velocity. This project report also presents the analysis of handoff for real data from the cellular network provider. The analysis made also for a mobile moving between two base stations with fixed velocity.